PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF INFORMATION AND DIGITAL COMPETENCE OF FUTURE TEACHERS (Psychology Travelogs, 2025)
The article examines the essence and structure of information and digital competence (ICC) as a key component of modern education and professional development of future teachers.The main approaches to defining ICT content were analyzed, in particular based on the European DigComp 2.2 Framework: information literacy, communication and interaction in the digital environment, digital content creation, digital security, digital problem solving and DigCompEdu (main areas of development of digital competence of a teacher: professional interaction; digital resources; learning and teaching; assessment; helping students to develop skills for safe and ethical behavior on the Internet; self-development).Five main components of information and digital competence were identified: information literacy, digital communication and collaboration, digital content creation, digital security and technology-based problem solving.Particular attention is paid to the factors of ICT development, including institutional (educational environment, material and technical base), pedagogical (content and methods of teaching), socio-psychological (motivation, digital culture), as well as state (professional standards, policy of digitalization of education).The specifics of the development of ICT of future teachers are outlined, which consists in a combination of technological, methodological and ethical readiness to use digital tools in the educational process. It is determined that the effective formation of information and digital competence of a future teacher involves the creation of an innovative educational environment, the development of digital creativity skills, critical thinking, ethics and security on the Internet.The results of the study emphasize that information and digital competence is a necessary condition for the professional self-realization of a teacher in the conditions of digital transformation of education and society in general.It is proven that information and digital competence enables a teacher to flexibly adapt to changes in educational formats, organize high-quality distance and blended learning, optimize access to educational content, ensuring inclusiveness and personalization of learning, use digital tools to increase student motivation, gamification and visualization of complex concepts, form digital literacy, critical thinking, information culture in students, improve their own qualifications through online courses, webinars, digital pedagogical communities.
Keywords: information and digital competence; digital literacy; future teachers; development factors; components; digitalization of education